Odpowiedzi

  • Użytkownik Zadane
2009-11-03T16:39:20+01:00
(2 √7)²=4×7=28
(3 √3/2)²=9×3/4=27/4=6 3/4
4 √5²=4×5=20
1/3 √6×3√6=6
7 ∛5³=7×5=35
(2 ∛3)³=8×3=24
3/ √5=(3√5)/5
-2/ √7=(-2√7)/7
(2 √2)/√3=(2√6)/3
-2/(3 √6)=(-2√6)/(3×6)=-√6/9
(-3 √10)/(5 √2)=(-3√20)/(5×2)=(-6√5)/10=(-3√5)/5
(-2 √5) /(3√10)=(-2√50)/(3×10)=(-10√2)/30=-√2/3
2009-11-03T17:55:20+01:00
(2 √7)²=4*7=28
(3 √3/2)²=9*¾=27/4=6¾
4 √5²=4*5=20
⅓√6*3√6=√36=6
7 ∛5³=7*5=35
(2 ∛3)³=8*3=24
3/√5=(3√5)/5
-2/√7=(-2√7)/7
(2√2)/√3=(2√6)/3
-2/(3√6)=(-2√6)/(3*6)=-2√6/18=-√6/9
(-3√10)/(5√2)=(-3√20)/(5*2)=(-6√5)/10=(-3√5)/5
(-2√5) /(3√10)=(-2√50)/(3*10)=(-10√2)/30=-√2/3